Effectiveness of interventions to reduce flour dust exposures in supermarket bakeries in South Africa. Issue 12 (4th June 2014) - Baatjies, Roslynn; Meijster, Tim; Heederik, Dick; Sander, Ingrid; Jeebhay, Mohamed F
Abstract : Rationale: A recent study of supermarket bakery workers in South Africa demonstrated that 25% of workers were sensitised to flour allergens and 13% had baker's asthma. Evidence on exposure reduction strategies using specifically designed interventions aimed at reducing the risk of baker's asthma is scarce. Objectives: The aim of this study was to evaluate the effectiveness of different control measures to reduce airborne flour dust exposure using a randomised design. Methods: A group-randomised study design was used to assign 30 bakeries of a large supermarket chain store to two intervention groups and a control group, of which 15 bakeries were studied. Full-shift environmental personal samples were used to characterise exposure to flour dust and wheat and rye allergens levels pre-intervention (n=176) and post-intervention (n=208). Results: The overall intervention effect revealed a 50% decrease in mean flour dust, wheat and rye allergen exposure. The reduction in exposure was highest for managers (67%) and bakers (47%), and lowest for counterhands (23%). For bakers, the greatest reduction in flour dust was associated with control measures such as the use of the mixer lid (67%), divider oil (63%) or focused training (54%). However, the greatest reduction (80%) was observed when using a combination of all control measures. Conclusions: A specially designed intervention strategy reduced both flour dust and allergen levels. Best results were observed when combining both engineering controls and training. Further studies will investigate the long-term health impact of these interventions on reducing the disease burden among this group of bakers.